P-B7 Balance of cellular and humoral immunity determines the level of protection by HIV vaccines in rhesus macaque models of HIV infection. (January 2016) - Fouts, Timothy; Bagley, Kenneth; Prado, Ilia; Bobb, Kathryn; Schwartz, Jennifer; Xu, Rong; Zagursky, Robert; Egan, Micheal; Eldridge, John; Labranche, Celia; Montefiori, David; Le Buanec, HéLèNe; et al.
Abstract : A guiding principle for HIV vaccine design has been that cellular and humoral immunity work together to provide the strongest degree of efficacy. However, three efficacy trials of Ad5-vectored HIV vaccines showed no protection. Transmission was increased in 2 of the trials, suggesting that this vaccine strategy elicited CD4+ T cell responses that provide more targets for infection, attenuating protection or increasing transmission. The degree to which this problem extends to other HIV vaccine candidates is not known. Here, we show that a gp120-CD4 chimeric subunit protein vaccine [full-length single chain (FLSC)] elicits heterologous protection against SHIV or SIV acquisition in three independent rhesus macaque repeated low-dose rectal challenge studies with SHIV162P3 or SIVmac251. Protection against acquisition was observed with multiple formulations and challenges. In each study, protection correlated with antibody dependent cellular cytotoxicity (ADCC) specific for CD4-induced epitopes (CD4i) provided that the concurrent anti-vaccine T cell responses were minimal. Protection was lost in instances where T cell responses were high or when the requisite antibody titers had declined. Our studies suggest that balance between a protective antibody response and antigen-specific T cell activation is the critical element to vaccine-mediated protection against HIV. Achieving and sustaining such a balance, while enhancing antibody durability, is the major challenge for HIV vaccine development, regardless of the immunogen or vaccine formulation.